Analisis Pengaruh Good Corporate Governance Dan Profitabilitas Terhadap Nilai Perusahaan Pada Bank Swasta Devisa Nasional Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2015-2019 - Wiwin Indah Sari; Haifah Haifah; Wiwik Fitria Ningsih (STIE Mandala Jember, 2021)
This study aims to analyze the effect of good corporate governance and profitability on firm value in National Private Foreign Exchange Banks listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Good corporate governance variable is proxied by the board of commissioners, board of directors, and audit committee, while profitability is proxied by net profit margin (NPM). The research sample was selected based on purposive sampling technique, so as to obtain a sample of 14 national foreign exchange private banks. The analytical method used is multiple regression analysis. The results showed that partially the board of commissioners, board of directors, audit committee, and profitability had no significant effect on firm value. Simultaneously, all the independent variables, namely the board of commissioners, the board of directors, the audit committee, and profitability have a significant effect on firm value.